Smoking Cessation in Chinese Patients Undergoing Thoracic Surgery: A Multicenter Prospective Observational Study - Jianxing He; Dingpei Han; Kun Qian; Weijie Guan; Ge Zhang; Weiqing Lu; Hecheng Li; Xiuyi Zhi (Tobacco Induced Diseases)
Introduction The multicenter CHAMPION study aimed to assess the impact of smoking cessation on post-operative complications (PCs) and smoking cessation patterns in Chinese patients undergoing lung surgery.